All Days 2004
DOI: 10.4043/16161-ms
|View full text |Cite
|
Sign up to set email alerts
|

Measured Horizontal Capacity of Suction Caissons

Abstract: Laboratory tests were conducted to study the behavior of suction caissons when loaded horizontally below the mudline. The experiments were performed using a 4-in. diameter caisson installed to a depth of 32 in. in normally consolidated kaolinite clay. The test prototype is representative of caisson geometries commonly used in mooring systems for deep offshore locations with soft seafloor sediments. Nine horizontal load tests were conducted with the loading cable attached at different points along the lower hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Yun and Bransby (2007b) reported the undrained vertical bearing capacities of skirted strip foundations in non-homogenous soft clay using 100 g centrifuge model tests. Coffman et al (2004) conducted a series of 1 g model tests to study the horizontal bearing Tables 3 and 4 show the comparisons of the vertical and horizontal bearing capacities, respectively. The error between the capacities from the FE analyses and previous studies was only 0.0%À5.5%.…”
Section: Validation Of Fe Analysesmentioning
confidence: 99%
“…Yun and Bransby (2007b) reported the undrained vertical bearing capacities of skirted strip foundations in non-homogenous soft clay using 100 g centrifuge model tests. Coffman et al (2004) conducted a series of 1 g model tests to study the horizontal bearing Tables 3 and 4 show the comparisons of the vertical and horizontal bearing capacities, respectively. The error between the capacities from the FE analyses and previous studies was only 0.0%À5.5%.…”
Section: Validation Of Fe Analysesmentioning
confidence: 99%
“…A gap has greater potential to be formed and remain open the higher the soil strength ratio su/γ'z (Britto and Kusakabe 1982;Coffman et al 2004;Supachawarote et al An experimental investigation of Mana/Gourvenec/Randolph reverse end bearing of offshore shallow foundations 6 2005). Analytical solutions (Britto and Kusakabe 1982) indicate that the minimum strength ratio necessary for the stability of an axisymmetric excavation in soft clay varies from around 0.25 to 0.18 for unsupported excavations with an excavation depth to diameter ratio of 0.1 to 0.5.…”
Section: Gappingmentioning
confidence: 99%
“…Although no literature is available regarding gapping along shallow skirted foundations, various authors have reported that large displacements are required for a gap to form along laterally loaded caissons (similar to skirted foundations but with larger embedment depth to diameter ratio, d/D) in normally consolidated soil, while for lightly and over consolidated soils a gap may appear immediately after lateral or inclined loading (Clukey et al, 1995;Randolph et al, 1998;Clukey et al, 2003;CoŠman et al, 2004). Clukey et al (1995) report results from a centrifuge study of the eŠect of gapping on the capacity of suction caissons in typical Gulf of Mexico normally consolidated soft clay under cyclic loading, but did not observe a critical load at which the caisson suddenly failed from gapping.…”
Section: Introductionmentioning
confidence: 99%
“…For this case, they proposed an intermediate mode of failure, between pure shearing along the skirt and the full reverse end bearing. CoŠman et al (2004) investigated the horizontal capacity of suction caissons in normally consolidated clay at 1 g and did not observe a distinct gap in the back side of the caisson after lateral displacements up to several times the caisson diameter, but observed a scarp on the back side of the caisson and a wedge of soil that slid downwards, maintaining contact with the caisson. Supachawarote et al (2005) reported three-dimensionalˆnite element analysis investigating the eŠect of gapping on the inclined pullout capacity of suction caissons and for an embedment ratio d/D=1.5 showed an average reduction in inclined undrained pullout capacity of 27z in lightly over consolidated soil.…”
Section: Introductionmentioning
confidence: 99%